IMPROVEMENT OF PROFESSIONAL TRAINING FUTURE TEACHERS BY MEANS FOREIGN LANGUAGE - L.P. Kadchenko (Academy of Cognitive and Natural Sciences, 2001)
Effectiveness of foreign languages studying in professional training of future teachers is possible due to the realization of the following trends in work: forming professional, pedagogical, and linguistic interests of students by contents of educational information studied by them; teaching multiform methods and ways of cognitive activity; bringing the contents of educational information into accord with interests, motives, demands and professional aims of students.